2021
DOI: 10.18494/sam.2021.3444
|View full text |Cite
|
Sign up to set email alerts
|

Taste Profile Characterization of Chinese Mitten Crab (Eriocheir sinensis) Meat Using Electronic Tongue Analysis

Abstract: An SA402B taste sensing system (electronic tongue) was used to evaluate the meat taste characteristics of three groups of Chinese mitten crab Eriocheir sinensis (H. Milne Edwards, 1853): those from the native culture area in the Yangcheng Lake, Yangcheng Lake-labeled crabs from the market, and those from aquaculture ponds. The electronic tongue data showed that umami was the most predominant taste in the steamed meat, followed by sweetness. The aftertaste of umami was clearly observed in all crab meat samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This lake provides ideal habitats for crab growth, giving Yangcheng Lake crab meat a clean and slightly sweet taste. "Yangcheng Lake Hairy Crab" remain the best-selling variety of hairy crabs in China, and are so reputed for the taste that people willingly pay high prices (USD 10-40 per individual vs. USD 1-5 per individual from other regions) for them [26]. Consumption of market-sized Chinese mitten crabs generally starts in September each year, with the peak period falling between October and November.…”
Section: Discussionmentioning
confidence: 99%
“…This lake provides ideal habitats for crab growth, giving Yangcheng Lake crab meat a clean and slightly sweet taste. "Yangcheng Lake Hairy Crab" remain the best-selling variety of hairy crabs in China, and are so reputed for the taste that people willingly pay high prices (USD 10-40 per individual vs. USD 1-5 per individual from other regions) for them [26]. Consumption of market-sized Chinese mitten crabs generally starts in September each year, with the peak period falling between October and November.…”
Section: Discussionmentioning
confidence: 99%
“…The ltrate was then extracted with a mixture of ethyl acetate and saturated salt water, and nally washed ve times with deionized water. Then the solution was concentrated by spin evaporation and separated by column chromatography 44,49,50 using an ethyl acetate and ethanol mixed solution (10 : 1, v/v) as the spreading agent (R f value of 0.59), and the liquid product was dried by spin evaporation to obtain a solid powder with an orange-yellow colour.…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al used SA402B to characterize Chinese mitten crab meat from three groups: the native culture area in Yangcheng Lake, Yangcheng Lake-labeled crabs from the market, and aquaculture ponds [ 89 ]. The E-tongue data showed that umami and sweetness were the main tastes in crab meat, while saltiness and bitterness varied in crabs from different geographic origins.…”
Section: Electronic Tongues In Bitterness Evaluationmentioning
confidence: 99%